Development of a research model to study the operability of a variable pitch fan aero engine in reverse thrust - Rajendran, David John; Bentley, David; Azamar Aguirre, Hasani; Tunstall, Richard; Pachidis, Vassilios (Global Power and Propulsion Society, 2020)
A rationale for the level of model fidelity required to provide the most representative flow field information to ascertain the feasibility of using a Variable Pitch Fan (VPF) in a modern high bypass ratio aero engine to generate reverse thrust is described in this paper. This is done by comparing the 3D RANS flow field solution for a newly developed reverse flow VPF design from two research models: i) isolated engine model in which the bypass duct, guide vanes, splitter and VPF are wrapped in an axisymmetric nacelle and placed in a generic far-field domain and b) integrated model in which the engine is installed to an airframe in landing configuration through a pylon and placed in a far-field domain bound by a rolling runway. The flow field solution obtained at an aircraft landing speed of 80 knots indicates that even though both models can predict the general flow patterns, there are substantial differences in parameters such as the amount of reverse stream, circumferential distribution of flow properties and flow development downstream of the engine. These differences impact the levels of reverse thrust generated, flow distortion entering the core engine and resultant airframe forces. This study makes the case that it is necessary to use an integrated model that includes a full engine nacelle installed on an airframe, to answer design questions for engineering the VPF system to generate reverse thrust.